Empowerment : a practical guide for success - Scott, Cynthia D. (Crisp Pub. Menlo PaarkUS, 1991)
Describes the process of creating an empowered organization. Identifies the key qualities of an empowered workplace and provides a survey for testing the level of empowerment.